Health Tourism Development Strategy through Business Process Modelling Using the APQC Framework - Erwin Erwin; Irving Vitra Paputungan (Jurnal Sistem Informasi Bisnis, 2026)
Introduction - Indonesia has experienced a surge in citizens seeking healthcare services abroad, resulting in a loss of foreign exchange of up to 165 trillion rupiah per year. This situation highlights the need for a competitive domestic health tourism development strategy.Purpose - The objective of this study is to develop a health tourism business process model based on the APQC Process Classification Framework (PCF) to create structured, efficient, and globally competitive services.Design/Methodology/Approach - The study employs a descriptive approach with process mapping using the APQC framework, which spans from strategic to operational levels. Data was obtained from literature reviews and conceptual analysis.Result/Finding - Findings indicate that regions such as Bali, Jakarta, Surabaya, Yogyakarta, Medan, Malang, and Manado possess diverse potential for health tourism development, including medical infrastructure, digital maturity, and unique cultural and natural features. The designed business process model illustrates service selection flows, actor interactions, and sector integration.Originality/Value - This study offers a new approach to health tourism business process modelling using the APQC framework, which has not been widely applied in Indonesia. Its contribution lies in the systematic design that can serve as a reference for the government and private sector.Limitation - This study is still limited to descriptive analysis using secondary data sources. Field validation or stakeholder involvement has not been conducted, so the effectiveness of the model needs further testing.